(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
The rapid expansion of digital tourism has changed the way individuals encounter cultural heritage, communicate with representatives of different communities and participate in tourism-related learning. Digital platforms, virtual tours, augmented reality, online museum resources, QR-based information systems and digital storytelling tools are no longer limited to destination promotion; they increasingly function as educational environments for developing cultural awareness and social communication skills. This article analyzes foreign and national research devoted to the development of cultural and social skills through digital tourism. The study is based on a comparative literature review of international scientific works, policy documents and national studies related to digital tourism, smart tourism, cultural heritage, tourism education and intercultural competence. The findings show that foreign research mainly emphasizes digital competence, intercultural communication, user experience, social inclusion and sustainable tourism education, whereas national research, particularly in Uzbekistan, focuses more on digitalization of tourism infrastructure, promotion of cultural heritage, smart tourism mechanisms and sustainable development of heritage destinations. The article concludes that digital tourism can become an effective pedagogical and socio-cultural tool if it is integrated with interactive learning, local cultural content, multilingual communication and community-based tourism practices.